2000
DOI: 10.1007/s100960050007
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors of Enterococcus faecalis and Enterococcus faecium Blood Culture Isolates

Abstract: Known and potential virulence factors of enterococcal blood culture isolates were studied using 89 Enterococcus faecalis and 24 Enterococcus faecium isolates. The prevalence of the respective factors was (Enterococcus faecalis vs. Enterococcus faecium): hemolysin 16% vs. 0%, gelatinase 55% vs. 0%, aggregation substance 63% vs. 13%, lipase 35% vs. 4%, hemagglutinin 97% vs. 0%. Deoxyribonuclease was not detected in any isolate. The study showed that hemagglutinin and lipase may represent additional virulence fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
76
0
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 18 publications
12
76
0
8
Order By: Relevance
“…Even though some studies failed to detect these genes in Enterococcus faecium (Duprè et al, 2003;Mannu et al, 2003), in our study, 13 Enterococcus faecium (5 %) carried asp and two (1 %) the ace determinants. Our results are in agreement with the literature concerning higher incidence of virulence genes (esp, asp, ace) among Enterococcus faecalis (Abriouel et al, 2008;Duprè et al, 2003;Elsner et al, 2000). Abriouel et al (2008) reported lower incidence of ace gene in enterococci from water samples as compared with clinical isolates, a finding contradicting our results, since 39 (56 %) water isolates were ace-positive, while only 15 (8 %) clinical isolates carried the gene.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Even though some studies failed to detect these genes in Enterococcus faecium (Duprè et al, 2003;Mannu et al, 2003), in our study, 13 Enterococcus faecium (5 %) carried asp and two (1 %) the ace determinants. Our results are in agreement with the literature concerning higher incidence of virulence genes (esp, asp, ace) among Enterococcus faecalis (Abriouel et al, 2008;Duprè et al, 2003;Elsner et al, 2000). Abriouel et al (2008) reported lower incidence of ace gene in enterococci from water samples as compared with clinical isolates, a finding contradicting our results, since 39 (56 %) water isolates were ace-positive, while only 15 (8 %) clinical isolates carried the gene.…”
Section: Discussionsupporting
confidence: 78%
“…The Enterococcus surface protein (Esp), encoded by the esp gene, acts as an adhesin and is involved in the formation of biofilms (Upadhyaya et al, 2011), although this association has not been not confirmed by other investigators (Comerlato et al, 2013). Many proteins have been implicated in enterococcal virulence (Elsner et al, 2000). The most commonly implicated are the aggregation substance (asp gene) enhancing the adherence to matrix proteins and the collagen-binding protein encoded by the ace gene (Duprè et al, 2003;Vankerckhoven et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence factors of E. faecalis, such as hemolysin, gelatinase, and enterococcal aggregation substance (EAS) play an important role in the bacterium's pathogenesis (4). However, the mechanism through which E. faecalis persists in the root canal is not well understood.…”
mentioning
confidence: 99%
“…The only virulence factors that were established in the strain were haemolytic activity and biofilm formation. It should be noted that significance of haemolysin as a virulence factor of enterococci has not been proved, as it has been shown that only 0-16 % of blood culture enterococcal isolates display haemolytic activity (Elsner et al, 2000). Moreover, haemolytic activity was more common in non-endocarditis clinical isolates and in hospital faecal isolates than among endocarditis isolates (Coque et al, 1995) and there was no significant association between 14-day mortality and the presence of haemolysin in enterococci (Vergis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%